Preservation of granulite in a partially eclogitized terrane: Metastable phenomena or local pressure variations? - Putnis, Andrew; Moore, J.; Prent, A.M.; Beinlich, Andreas; Austrheim, H. (ELSEVIER, 2021)
Granulite is preserved over large areas of partially eclogitized and hydrated rocks on Holsnøy, Bergen Arcs, Norway. The interfaces between granulite and eclogite are sharp on a hand-specimen scale and contain microstructural and compositional evidence for the mechanism of eclogitization. The interface studied here is undeformed with a continuous foliation from granulite through an eclogite ‘finger’ that protrudes into the granulite. Diopside in the granulite evolves continuously to omphacite in eclogite by increasing jadeite composition at a well-defined sequence of microstructures that involve pyroxene-amphibole intergrowths and symplectites. Plagioclase in the granulite develops a high density of zoisite and kyanite inclusions that increase in abundance prior to plagioclase breakdown in eclogite. The transition between granulite and eclogite is interpreted as indicating a pressure gradient. The observation that granulite is preserved adjacent to eclogite although it shows sufficient evidence of hydration such that metastability may not be a factor, suggests that eclogitization involves the generation of increased pressure due to reaction and rock weakening. The pyroxene and feldspar microstructures in the transition zone between granulite and eclogite are very similar to the transition zones between granulite and amphibolite elsewhere in the Bergen Arcs. Localized variation in pressure could be an explanation for concurrent eclogitization and amphibolitization of granulite at the same crustal level during orogenesis.